Inner-city street traders: Legality and spatial practice - Makhetha, Puleng. Rubin, Margot. (Wits University Press, 2014)
A mix of respected academics, practising urban planners and experienced policymakers offer compelling overviews of the rapid and complex spatial developments that have taken place in Johannesburg since the end of apartheid, along with tantalising glimpses into life on the streets and behind the high walls of this diverse city. The book has three sections. Section A provides an overview of macro spatial trends and the policies that have infl uenced them. Section B explores the shaping of the city at district and suburban level, revealing the peculiarity of processes in different areas. This analysis elucidates thelarger trends, while identifying shifts that are not easily detected at the macro level. Section C is an assembly of chapters and short vignettes that focus on the interweaving of place and identity at a micro level.
Keywords: Street traders